DETERMINATION OF NITRATE AND NITRITE CONTENT IN ZONAR MILK SERUM AND DERIVED DAIRY DRINKS USING ION-PAIR REVERSED-PHASE HIGH PERFORMANCE LIQUID CHROMATOGRAPHY - FILIP, Miuța; PRODAN, Doina; MOLDOVAN, Marioara; VLASSA, Mihaela (Studia Universitatis Babeș-Bolyai Chemia, 2019)
The presence of nitrite and nitrate in milk and dairy products may cause serious health problems for consumers. Thus, a simple and accurate ion-pair reversed-phase high performance liquid chromatographic (IP-RP-HPLC) method has been developed and validated for determination of nitrite and nitrate in some dairy drinks based on Zonar Milk Serum. The separation was achieved on a Synergy Hydro-RP polar endcapped C18, 80Å, 4mm (250 ´ 4.6 mm) column using isocratic elution with 0.01M n-octylamine and methanol, 90:10 (v/v) at pH=7; with flow rate of 1 mL·min-1 and detection at 214 nm and 25°C. A linear response (R2 ≥ 0.9994) was observed in the range between 3.125 and 75 µg mL-1 for the nitrite and nitrate standard solutions. The limits of detection (LOD) and quantification (LOQ) were found as 0.25 µg mL-1 and 0.8 µg mL-1 for nitrite and 0.4 µg mL-1 and 1.2 µg mL-1 for nitrate, respectively. The method was validated according to ICH guidelines with respect to selectivity, linearity, detection and quantitation limits, accuracy and precision. The good analytical performance verified for this method indicates that it is suitable for the monitoring of nitrite and nitrate in dairy drinks based on Zonar Milk Serum.